2020
DOI: 10.3390/rs12071058
|View full text |Cite
|
Sign up to set email alerts
|

Regional Mapping of Essential Urban Land Use Categories in China: A Segmentation-Based Approach

Abstract: Understanding distributions of urban land use is of great importance for urban planning, decision support, and resource allocation. The first mapping results of essential urban land use categories (EULUC) in China for 2018 have been recently released. However, such kind of national maps may not sufficiently meet the growing demand for regional analysis. To address this shortcoming, here we proposed a segmentation-based framework named EULUC-seg to improve the mapping results of EULUC at the city scale. An obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 22 publications
1
42
0
Order By: Relevance
“…In this study, it can be found that the POI features had the greatest contributions in the EULUC-Nanjing mapping (Table 7 and Figure 9). However, Tu et al [26] pointed out that compared with POI data, the features obtained from Sentinel-2 imagery were the main factors affecting the classification performance. This may be because this study used the regenerated POI data by overcoming the problem of unbalanced distribution and extracted the POI spatial features.…”
Section: Contribution Of Different Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, it can be found that the POI features had the greatest contributions in the EULUC-Nanjing mapping (Table 7 and Figure 9). However, Tu et al [26] pointed out that compared with POI data, the features obtained from Sentinel-2 imagery were the main factors affecting the classification performance. This may be because this study used the regenerated POI data by overcoming the problem of unbalanced distribution and extracted the POI spatial features.…”
Section: Contribution Of Different Featuresmentioning
confidence: 99%
“…The classification accuracy for 27 validation cities ranges from 40.4% to 82.9% for Level I, and from 34% to 80% for Level II. However, the relatively lower accuracy of EULUC-China may not sufficiently meet the growing demands for urban planning, environmental monitoring, and other aspects at local to regional scopes [26], which can be attributed to the following aspects. Firstly, the buffer thresholds of roads for generating urban parcels were simply divided into major and minor categories without details assigned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of big data, many new data sources were introduced into the land-use classification field. Mobile phone record data, floating car data, social media data, and other big data have shown their importance in land-use classification [3,[12][13][14][15][16][17][18]. Although the inclusion of socioeconomic data can improve the accuracy of land-use classification, studies combining image data and multiple-source Internet open data to classify urban land use are relatively rare, and few studies have been conducted in large cities.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the spatially mixed vegetation structures, seasonal variations of vegetation, and the temporal inconsistency between Landsat and Sentinel data, the classification accuracy for these vegetation types is relatively low [28]; (2) Usage of limited features. The predictors are mainly depending on Sentinel-2 based features such as spectral and derived remote sensing indices, without considering other information that is highly correlated with land covers such as nighttime light (NTL) and incident microwave radiation [29,30]; (3) Uncertainty of models. A unified model is used to classify global land cover, which may lead to biased performance for localized experiments.…”
Section: Introductionmentioning
confidence: 99%